Renal replacement therapy may be initiated in patients with hepatorenal syndrome who are not transplant candidates - Laura Donohue (Clinical Research In Practice: The Journal of Team Hippocrates, 2022)
A clinical decision report using: Allegretti AS, Parada XV, Eneanya ND, et al. Prognosis of Patients with Cirrhosis and AKI Who Initiate RRT. Clin J Am Soc Nephrol. 2018;13(1):16-25. https://doi.org/10.2215/CJN.03610417 for a patient being considered for RRT who was not yet a candidate for liver transplant.